Enhancing Filipino Senior High School Students' Conceptual Understanding of Philippine Folk Dance Using the iSAYAW Web Application - Simon, Christian Louie C.; Pinlac, Jelene T.; Regala, Wendie A.; Dela Peña, Ramil D.; Tolentino, Julius Ceazar G.; Soriano, Lourdes P. (Future Science / FSH-PH Publications, 2024)
The introduction of Philippine folk dance (PFD) has been a very challenging pursuit by many physical educators in the Philippines. Thus, a continuous exploration of potential instruction powered by digital technologies is currently being explored. Hence, this study employed iSAYAW - a web-based system teaching-learning material for teaching PFD. This study utilized a quantitative action research approach, employing a one-group pre-test and post-test inquiry. A 50-item researcher-made test was administered to assess students' conceptual understanding of Philippine folk dance before and after the intervention. A class of 45 students was identified to gain the lowest mean score during the pre-test, which was the reason for the four-week implementation of iSAYAW. After the intervention, it was found that the post-test scores showed a notable increase compared to pre-test scores, indicating that the web-based learning material effectively enhanced students' conceptual understanding of PFD and contributed to their learning of the concepts. Hence, it was revealed that students' experiences were enjoyable and that using the app was helpful for independent learning. It led them to improve their scores as it offers lessons that the teachers are not teaching sometimes. In contrast, this application mitigates the learning process of the PFD concepts. However, students faced challenges, particularly with their internet connection limiting their learning experience with the application. Hence, it is recommended that students explore iSAYAW, expand its content, extend usage duration, include multiple grade levels, and promote cultural heritage to enhance learning and appreciation of Philippine folk dance.